Impact of currency reform on Chinese external trade - Aftab, Muhammad; Ismail, Izlin (Institute of China Studies, 2018)
This paper discusses the impact of Chinese authorities’ 2005 decision to abandon the fixed exchange rate regime on China’s international trade. After such reform, exchange rate volatility tend to arise and that can affect a country’s international trade. As the Chinese economy is highly reliant on international trade, the consequences of exchange rate reform may be serious. Our findings reveal that the influence of exchange rate changes is negative only on China’s imports. There is no such influence for its exports. Therefore, the exchange rate fluctuations after the 2005 reform are encouraging for China’s trade balance. On the other hand, there is no significant effect on exchange rate volatility.